Complex Concentrated Alloy Catalyst of AlCrFeCoNi for Heterogeneous degradation of Rhodamine B - Sembiring, Kiky Corneliasari; Fahrezi, Irgi Ahmad; Muhdarina, Muhdarina; Afandi, Ahmad (Bulletin of Chemical Reaction Engineering & Catalysis, 2024)
The Fe-based catalysts have attracted good attention due to their earth abundance and low toxicity with good Fenton-like performance. However, the narrow pH working range and iron-containing sludge produced during the reaction drove the necessary of developing a potential catalyst in the corresponding application. High entropy alloy that now expands to complex concentrated alloy (CCA) represents a new class of material owing to a broader range of functional and structural properties. A new application of CCA as a catalyst for catalytic degradation of azo dyes has already been a scientific research hotspot. AlCrFeCoNi CCA powder has been successfully synthesized by mechanical alloying (MA) method using a vertical planetary ball mill. Based on the characterization, the catalyst possessed a spherical morphology with a particle size range of 3.5-12.6 mm. The catalyst exhibited photo-Fenton performance up to 85.3% which would be a promising Fenton-like catalyst for wastewater treatment. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).